Case Report: Two cases of staged combined treatment for complex skull-exposing wounds: synergistic effects of mechanical tension and moist wound healing - Lin, Jianqiong; Ma, Yanfei; Zeng, Xiaohong; Zhang, Yan; Liu, Hongyuan (Frontiers in Medicine, 2025)
Complex skull-exposing wounds complicated by repeated surgical failures, implant-associated infections, and a history of targeted drug therapy present substantial challenges for reconstruction. This study retrospectively analyzed two such cases to evaluate the clinical outcomes of a staged treatment strategy integrating a sustained skin-stretching device (SSD) with moist wound therapy. Case 1, with four previous failed surgeries, achieved complete closure within 40 days, with no recurrence during 6 months of follow-up. Case 2, after three debridement procedures, achieved closure in 45 days with stable scar formation and no dehiscence at 6 months. The treatment protocol incorporated SSD with silver ion dressings, recombinant human basic fibroblast growth factor (rh-bFGF), mussel adhesive protein-based dressings, and Moist Exposed Burn Ointment (MEBO), supplemented by surgical debridement as required. Controlled mechanical tension and an optimized moist microenvironment promoted progressive wound edge advancement, effective infection control, and tissue regeneration. The findings indicate that staged mechanical traction combined with moist wound dressings may represent a minimally invasive and effective approach for managing complex cranial wounds.